Suitability of the expanded indication criteria for the treatment of early gastric cancer by endoscopic submucosal dissection: Japanese multicenter large-scale retrospective analysis of short- and long-term outcomes. (April 2014) - Nakamura, Kazuhiko; Honda, Kuniomi; Akahoshi, Kazuya; Ihara, Eikichi; Matsuzaka, Hiroshi; Sumida, Yorinobu; Yoshimura, Daisuke; Akiho, Hirotada; Motomura, Yasuaki; Iwasa, Tsutomu; Komori, Keishi; Chijiiwa, Yoshiharu; et al.
Abstract: Objective. The criteria for endoscopic resection for early gastric cancer include absolute and expanded indications. Consensus already exists for the absolute indications. However, the suitability of the expanded indications must be validated by long-term outcome analyses since such lesions have only recently become resectable with the development of endoscopic submucosal dissection. The aim of this study is to clarify the suitability of the expanded indications for the treatment of early gastric cancer with endoscopic submucosal dissection. Materials and methods. The medical records of 1161 patients with early gastric cancers (1332 lesions) treated by endoscopic submucosal dissection and meeting the criteria for absolute or expanded indications without additional treatment with gastrectomy were divided into absolute indication group or expanded indication group. Results. Complete resection rates were 96.4% and 93.4% in absolute and expanded indication groups, respectively, with no significant differences between the groups. Delayed bleeding rates were significantly higher in the expanded indication group, whereas all cases were successfully managed conservatively. The 5-year overall survival and recurrence-free rates were 93.7%/99.77% and 90.49%/98.90% in the absolute and the expanded indication groups, respectively, with no significant differences between the groups for either measure. Multivariate analyses revealed that affected horizontal margin and tumor location were independent predictive factors for recurrence. Conclusion. The expanded indication group showed excellent post-endoscopic submucosal dissection short-term and long-term outcomes compared with the absolute indications group, demonstrating that expanded indications are suitable for endoscopic submucosal dissection for early gastric cancer.